Digital Libraries and the Philippines' Strategic Roadmap for the ICT Sector - Diaz De Rivera, Angelo Timoteo M. (Journal of Philippine Librarianship, 2009)
Discusses seven guiding principles of the Philippine strategic ICT roadmap and provides a situationer on the Philippines in cyberspace such as: information infrastructure, human capital, eBusiness, eGovernment, legal and regulatory situation. Envisions some Philippine agenda on strategic ICT programs for the country.
Keywords: ICT